Health policy and system support to optimise community health worker programmes: an abridged WHO guideline. Issue 12 (December 2018) - Cometto, Giorgio; Ford, Nathan; Pfaffman-Zambruni, Jerome; Akl, Elie A; Lehmann, Uta; McPake, Barbara; Ballard, Madeleine; Kok, Maryse; Najafizada, Maisam; Olaniran, Abimbola; Ajuebor, Onyema; Perry, Henry B; et al.
Summary: Optimising community health worker (CHW) programmes requires evidence-based policies on their education, deployment, and management. This guideline aims to inform efforts by planners, policy makers, and managers to improve CHW programmes as part of an integrated approach to strengthen primary health care and health systems. The development of this guideline followed the standard WHO approach to developing global guidelines. We conducted one overview of reviews, 15 systematic reviews (each one on a specific policy question), and a survey of stakeholders' views on the acceptability and feasibility of the interventions under consideration. We assessed the quality of systematic reviews using the AMSTAR tool, and the certainty of the evidence using the GRADE methodology. The overview of reviews identified 122 eligible articles and the systematic reviews identified 137 eligible primary studies. The stakeholder perception survey obtained inputs from 96 respondents. Recommendations were developed in the areas of CHW selection, preservice education, certification, supervision, remuneration and career advancement, planning, community embeddedness, and health system support. These are the first evidence-based global guidelines for health policy and system support to optimise community health worker programmes. Key considerations for implementation include the need to define the role of CHWs in relation to other health workers and plan for the health workforce as a whole rather than by specific occupational groups; appropriately integrate CHW programmes into the general health system and existing community systems; and ensure internal coherence and consistency across different policies and programmes affecting CHWs.